2014
DOI: 10.1152/jn.00221.2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of surround suppression in primary visual cortex and lateral geniculate nucleus of the cat

Abstract: In the primary visual cortex (V1), a neuronal response to stimulation of the classical receptive field (CRF) is predominantly suppressed by a stimulus presented outside the CRF (extraclassical receptive field, ECRF), a phenomenon referred to as ECRF suppression. To elucidate the neuronal mechanisms and origin of ECRF suppression in V1 of anesthetized cats, we examined the temporal properties of the spatial extent and orientation specificity of ECRF suppression in V1 and the lateral geniculate nucleus (LGN), us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…Researchers manipulating the temporal separation between the center patch and the oriented context found that, although the tilt illusion decreases as the stimulus onset asynchrony increases, it completely disappears only when the context precedes the center beyond about 300 ms (Corbett, Handy, & Enns, 2009;Durant & Clifford, 2006;Matin, 1974). Further, neurophysiological results support the finding that neurons are suppressed not only during the presentation of the context (Knierim & van Essen, 1992;Lamme, 1995;Zipser et al, 1996), but up to almost 200 ms after its disappearance (Ishikawa, Shimegi, Kida, & Sato, 2010;Shimegi et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Researchers manipulating the temporal separation between the center patch and the oriented context found that, although the tilt illusion decreases as the stimulus onset asynchrony increases, it completely disappears only when the context precedes the center beyond about 300 ms (Corbett, Handy, & Enns, 2009;Durant & Clifford, 2006;Matin, 1974). Further, neurophysiological results support the finding that neurons are suppressed not only during the presentation of the context (Knierim & van Essen, 1992;Lamme, 1995;Zipser et al, 1996), but up to almost 200 ms after its disappearance (Ishikawa, Shimegi, Kida, & Sato, 2010;Shimegi et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
“…This strongly manifested and rapidly aroused tilt illusion is supported by data directly recorded from the primary visual cortex of primates and cats. Neuron responses to the CRF stimulus surrounded by an isooriented context start to decrease no more than about 20 ms from the onset of the neuron responses to the CRF stimulus only or to the CRF stimulus with a orthogonally oriented context (Bair, Cavanaugh, & Movshon, 2003;Knierim & van Essen, 1992;Müller, Metha, Krauskopf, & Lennie, 2003;Nothdurft, Gallant, & van Essen, 1999;Shimegi et al, 2014, but see Zipser, Lamme, & Schiller, 1996, who reported a slightly longer onset latency at about 80 ms). Consistently, surround suppression, as indicated by the reduction of evoked magnetic responses in the human visual cortex, is also accompanied with a small response delay (Ohtani, Okamura, Yoshida, Toyama, & Ejima, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Several combinations of parameters gave rise to oscillatory IRFs (brighter colors); among these, IRF oscillations in the alpha (8–13 Hz) frequency range were particularly frequent (red colors). In particular, alpha-band IRF oscillations systematically arose when τ and ΔT lay in their “biologically plausible” range of respectively 15–25 ms [1518] and 10–15 ms [1921].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to temporal dynamics, most neurophysiological studies have measured the contrast response functions of V1 neurons using luminance gratings drifting at various temporal frequencies, and find strongest suppression of V1 CRF responses from high temporal frequency surrounds 66 67 . Those neurophysiological studies that have examined explicitly the time lag/delay between center and surround responses have used reverse correlation techniques, and find that the suppressive surround effects in V1 neurons peak at around 80 ms after the stimulus onset 68 with the ERF suppression lagging by up to 60–100 ms 41 42 44 68 69 70 71 . For area MT neurons, the inhibitory component of the surround response was found to lag ~10 ms after the center response 72 .…”
Section: Discussionmentioning
confidence: 99%